Peran Guru dalam Implementasi Konsep Dasar Kebijakan Pendidikan di Sekolah - Alfath, Irsyad; Fauziah, Fira Nuril; Septiana, Amelia; Aulia, Nurjahratul (Lembaga Yasin AlSys, 2023)
This article discusses the role of the teacher in implementing the basic concepts of education policy in schools. This article was developed through literature studies, the use of books and journals and other documents related to this article aims to provide an overview of the teacher's role in implementing the basic concepts of education policy in schools using an independent learning curriculum. Teachers must have the knowledge, skills and values that are relied upon. Teachers master the latest methods, strategies and learning media. Participants can easily understand the subject matter delivered by teachers at school. Curriculum is a set of subjects and various educational programs implemented by every level of education.